The perceptions of nurses towards barriers to the safe administration of medicines in mental health settings. Issue 6 (26th March 2014) - Hemingway, Steve; McCann, Terence; Baxter, Hazel; Smith, George; Burgess‐Dawson, Rebecca; Dewhirst, Kate
Abstract : The purpose of this study was to investigate perceptions of barriers to safe administration of medicines in mental health settings. A cross‐sectional survey was used, and 70 mental health nurses and 41 students were recruited from a mental health trust and a university in Yorkshire, UK. Respondents completed a questionnaire comprising closed‐ and open‐response questions. One item, which contained seven sub‐items, addressed barriers to safe administration of medication. Seven themes—five nurse‐ and prescriber‐focused and two service user‐focused—were abstracted from the data, depicting a range of barriers to safe administration of medicines. Nurse‐ and prescriber‐focused themes included environmental distractions, insufficient pharmacological knowledge, poorly written and incomplete medication documentation, inability to calculate medication dosage correctly, and work‐related pressure. Service user‐focused themes comprised poor adherence to medication regimens, and cultural and linguistic communication barriers with service users. Tackling medication administration error is predominantly an organizational rather than individual practitioner responsibility.